Peningkatan Pemahaman Konsep Manajemen Bagi Masyarakat Nelayan Di Laut Argapura, Distrik Jayapura Selatan, Kota Jayapura - C.L. Rumbiak (indonesia), Grace; Murwaniputri (indonesia), Hesti; Samosir (indonesia), Thesa Permatsari (JURNAL KASTARA, 2023)
The fishing community in Argapura Laut, South Jayapura District, Jayapura City has a settlement pattern that is above sea water, so the connecting road there is a rafting road. The condition of the existing jeramba road depends on the economy of the existing community. Each house has responsibility for the rapids around its house. The economic conditions of the people in Argapura Laut are very varied so it is very necessary to increase knowledge about management. The livelihood of the people in Argapura Laut is dominated by fishermen. The concept of fishermen there is fishing with basic fishing techniques. The aim of this service is to increase knowledge and understanding of the application of management concepts for the fishing community in Argapura Laut, South Jayapura District, Jayapura City. The method used is outreach and training on the implementation of POAC for the community. The expected result is that people have knowledge and understanding of management science and concepts and can apply them in everyday life so that people can maximize what is meant by effective and efficient.